2011
DOI: 10.1016/j.devcel.2011.08.017
|View full text |Cite
|
Sign up to set email alerts
|

ATXN1 Protein Family and CIC Regulate Extracellular Matrix Remodeling and Lung Alveolarization

Abstract: Summary Although expansion of CAG repeats in ATAXIN1 (ATXN1) causes Spinocerebellar ataxia type 1, the functions of ATXN1 and ATAXIN1-Like (ATXN1L) remain poorly understood. To investigate the function of these proteins, we generated and characterized Atxn1L−/− and Atxn1−/−; Atxn1L−/− mice. Atxn1L−/− mice have hydrocephalus, omphalocoele and lung alveolarization defects. These phenotypes are more penetrant and severe in Atxn1−/−; Atxn1L−/− mice, suggesting that Atxn1 and Atxn1L are functionally redundant. Upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
146
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(157 citation statements)
references
References 48 publications
11
146
0
Order By: Relevance
“…DEVELOPMENT 3966 a mouse model of spinocerebellar ataxia (Fryer et al, 2011) and in experiments with cultured mammalian cells (Dissanayake et al, 2011). We demonstrate that Cic lifetime is reduced in response to Torso RTK signaling in the Drosophila embryo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DEVELOPMENT 3966 a mouse model of spinocerebellar ataxia (Fryer et al, 2011) and in experiments with cultured mammalian cells (Dissanayake et al, 2011). We demonstrate that Cic lifetime is reduced in response to Torso RTK signaling in the Drosophila embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with cultured human cells and in a mouse model of spinocerebellar ataxia demonstrated that RTKs also counteract gene repression by Cic in vertebrates (Dissanayake et al, 2011;Fryer et al, 2011), but the mechanisms responsible for this effect are still poorly understood. Here, we investigate the RTK-dependent control of Cic in the early Drosophila embryo, the system where Cic was originally identified (Jiménez et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these functions, in lung cancer, HOTAIR has been identified as a scaffold to facilitate the binding of E3 ubiquitinylases and corresponding substrates Ataxin-1 and Snurportin ( Figure 1C) (68). Ataxin-1 is essential for lung alveolization and therefore, HOTAIR may promote dedifferentiation of lung epithelial cells (69). Forced expression of HOTAIR in non-transformed breast and lung cancer cell lines has been shown to promote growth in Figure 1.…”
Section: Hox Antisense Intergenic Rna (Hotair)mentioning
confidence: 99%
“…In a mouse model of SCA1, a modest exercise regimen extends longevity by reducing CIC levels in the brainstem. CIC loss through genetic perturbation also mitigates multiple SCA1 phenotypes in this model (Fryer et al 2011). …”
Section: Spinocerebellar Ataxia Typementioning
confidence: 99%